2020
DOI: 10.1007/s00068-020-01537-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone metabolism is a key factor for clinical outcome of tibial plateau fractures

Abstract: Purpose Given that tibial plateau fractures (TPF) are rare, they may pose a challenge to the treating surgeon due to their variety of complex fracture patterns. Numerous studies have identified potential fracture-specific, surgery-related, and patient-related risk factors for impaired patient outcomes. However, reports on the influence of bone metabolism on functional outcomes are missing. Methods In a retrospective multicenter cohort study, 122 TPF of 121 patients were analyzed with respect to radiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
0
12
0
4
Order By: Relevance
“…In a retrospective, multicenter cohort study from the Fracture Committee of the German Knee Society, 122 tibial plateau fractures have been followed clinically and radiographically for almost 3 years. In the current issue, it has been reported that in more than 95% clinical as well as radiological outcomes were good or even excellent [11]. Interestingly, Krause et al found that impaired bone metabolism is an important risk factor for poor outcomes [11].…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In a retrospective, multicenter cohort study from the Fracture Committee of the German Knee Society, 122 tibial plateau fractures have been followed clinically and radiographically for almost 3 years. In the current issue, it has been reported that in more than 95% clinical as well as radiological outcomes were good or even excellent [11]. Interestingly, Krause et al found that impaired bone metabolism is an important risk factor for poor outcomes [11].…”
mentioning
confidence: 86%
“…In the current issue, it has been reported that in more than 95% clinical as well as radiological outcomes were good or even excellent [11]. Interestingly, Krause et al found that impaired bone metabolism is an important risk factor for poor outcomes [11]. This entity is of high importance as a large percentile of our fractures will be accounted to an elderly population.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The operative treatment of tibial plateau fractures remains to be a challenging task and current outcomes seem to provide the potential for further improvement [1][2][3][4]. For optimal final results, next to the injury mechanism and the underlying soft tissue trauma, a thorough study of the radiographic imaging material is paramount in the preparation of the surgical strategy [1,5,6]. As practiced in many other anatomic regions, classification systems provide one major foundation Tobias Dust, Maximilian J. Hartel contributed equally and, therefore, share first authorship.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increased difficulty in manipulating fracture fragments as healing progresses, cancellous bone loss, occurring as early as five days post injury in the fractured tibial plateau [ 3 ], may also contribute to impaired fracture reduction. Maintenance of fracture reduction is multifactorial and may be affected by factors such as fracture severity, bone quality, surgical technique, and patient activities [ 4 , 5 , 6 ]. Indeed, such patient factors may, in some circumstances, lead to options such as total knee replacement or nonoperative management being considered [ 7 ].…”
Section: Introductionmentioning
confidence: 99%